2014
DOI: 10.1080/13102818.2014.972147
|View full text |Cite
|
Sign up to set email alerts
|

Association of single nucleotide polymorphism at position −308 of the tumor necrosis factor-alpha gene with ankylosing spondylitis and rheumatoid arthritis

Abstract: In this study, we analyzed the putative association between the −308 G/A polymorphism in the promoter region of the tumor necrosis factor (TNF) α gene (rs1800629) and chronic inflammatory arthritis in the Bulgarian population. A case-control study was carried out on 58 patients with ankylosing spondylitis (AS), 108 rheumatoid arthritis (RA) patients and 177 healthy subjects. −308 G/A TNF-α genotypes of patients and controls were determined by restriction fragment length polymorphism polymerase chain reaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
4
11
1
6
Order By: Relevance
“…The found assocaitions for TNF (rs1800629) [ 19 22 ], TNFRSF1A (rs4149570) [ 23 ], and IL23R (rs11209026) [ 24 33 ] are in agreement with other case-control studies. Furthermore, Zhao et al found that the variant allele of NLRP3 (rs4612666) was associated with increased risk of AS in Chinese patients [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…The found assocaitions for TNF (rs1800629) [ 19 22 ], TNFRSF1A (rs4149570) [ 23 ], and IL23R (rs11209026) [ 24 33 ] are in agreement with other case-control studies. Furthermore, Zhao et al found that the variant allele of NLRP3 (rs4612666) was associated with increased risk of AS in Chinese patients [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, in a cohort of Argentinean patients with RA, the −308A allele was neither associated with suscetibility to RA nor with the course and outcome of the disease (Aranda et al 2014 ). In addition, there was no significant association between −308 G/A polymorphism and RA risk in a cohort of Bulgarian population (Manolova et al 2014 ).…”
Section: Association Between Tnf-α Genetic Polymorphisms and Autoimmumentioning
confidence: 99%
“…Genotyping for the -308G/A polymorphism in the TNFA gene (rs1800629) was performed by restriction fragment length polymorphisms (RFLP) analysis of PCR fragment amplified using the modified forward primer 5-AGG CAA TAG GTT TTG AGG GCC AT 3 and the reverse primer 5-TTG GGG ACA CAC AAG CAT CAA GG 3 to create a restriction site for the NcoI enzyme as described by Manolova et al (13). Restriction enzyme of Nco1 (Thermo Scientific) digestion with the PCR product was carried out overnight at 37°C and then analyzed on a 3% agarose gel.…”
Section: Genetic Analysismentioning
confidence: 99%